2017
DOI: 10.1590/s1806-92902017000600001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with butyrate and probiotic on the survival of Pacific white shrimp after challenge with Vibrio alginolyticus

Abstract: This study evaluated the performance, immunology, and survival of the Pacific white shrimp Litopenaeus vannamei to experimental challenge to Vibrio alginolyticus based on the use of the probiotic Lactobacillus plantarum and the combined use of probiotic and butyrate. Four different diets resulted from the addition of additives: butyrate, probiotic, butyrate + probiotic, and control (no additives). The attractiveness of the diets was assessed by the percentage of positive choices and rejections, using a dual-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…Dietary supplementation of carbohydrates is a way to modulate microbial fermentation and promote butyrate production in the gut, which consequently improves health status (Sato et al, 2017). Recent studies in aquatic animals have demonstrated the roles of butyrate in improving growth performance, feed efficiency, immune responses, disease resistance, and survival rate, as well as in modulating gut microbiota (Gao et al, 2011;Robles et al, 2013;Liu B. et al, 2014;Estensoro et al, 2016;Rimoldi et al, 2016;Silva et al, 2016a,b;Terova et al, 2016;Ebrahimi et al, 2017;Piazzon et al, 2017;Ramírez et al, 2017;Tian et al, 2017;Ali et al, 2018;Rimoldi et al, 2018). For these reasons, the selection of a prebiotic capable of promoting the growth of butyrate-producing bacteria is necessary to enhance survival rate and improve aquaculture production.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of carbohydrates is a way to modulate microbial fermentation and promote butyrate production in the gut, which consequently improves health status (Sato et al, 2017). Recent studies in aquatic animals have demonstrated the roles of butyrate in improving growth performance, feed efficiency, immune responses, disease resistance, and survival rate, as well as in modulating gut microbiota (Gao et al, 2011;Robles et al, 2013;Liu B. et al, 2014;Estensoro et al, 2016;Rimoldi et al, 2016;Silva et al, 2016a,b;Terova et al, 2016;Ebrahimi et al, 2017;Piazzon et al, 2017;Ramírez et al, 2017;Tian et al, 2017;Ali et al, 2018;Rimoldi et al, 2018). For these reasons, the selection of a prebiotic capable of promoting the growth of butyrate-producing bacteria is necessary to enhance survival rate and improve aquaculture production.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the earlier researches on probiotics studies in aquatic animals were performed with the dietary inclusion of Bacillus and Lactobacillus species (Ambas, Fotedar & Buller, 2017; Ambas, Suriawan & Fotedar, 2013; Kongnum & Hongpattarakere, 2012; Zheng et al, 2017). However, a very few studies highlighted the importance of using C. butyricum as possible dietary probiotic candidate for crayfish (Ramírez et al, 2017). Results conducted with C. butyricum as dietary probiotic supplements demonstrated positive influence on growth and immune parameters of fish, chicken, piglet etc.…”
Section: Discussionmentioning
confidence: 99%
“…Then a serial dilution and subsequent plate counts were performed to obtain the desire bacterial concentration. The bacteria ( C. butyricum ) were then added at 10 7 CFU/mL per kg of feed as described in previous studies (Ramírez et al, 2017) and mixed uniformly. Pellet were prepared with mince mixture followed by vacuum drying oven at 37 °C for overnight and storage at 4 °C until used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations